Adjunctive tianeptine treatment for bipolar disorder: A 24-week randomized, placebo-controlled, maintenance trial. (April 2019) - Kauer-Sant'Anna, Márcia; Frey, Benicio N; Fijtman, Adam; Loredo-Souza, Ana C; Dargél, Aroldo A; Pfaffenseller, Bianca; Wollenhaupt-Aguiar, Bianca; Gazalle, Fernando K; Colpo, Gabriela D; Passos, Ives C; Bücker, Joana; Walz, Júlio C; et al.
Objective: The purpose of this study was to assess the efficacy and tolerability of tianeptine as an adjunctive maintenance treatment for bipolar depression. Methods: This is a multicenter double-blind randomized placebo-controlled maintenance trial of adjunctive tianeptine 37.5 mg/day. Participants ( n =161) had a Montgomery-Asberg Depression Rating Scale ⩾12 at entry. After eight weeks of open-label tianeptine treatment, those who responded to tianeptine ( n =69) were randomized to adjunctive tianeptine ( n =36) or placebo ( n =33) in addition to usual treatment. Kaplan-Meier estimates and the Mantel-Cox log-rank test were used to evaluate differences in time to intervention for a mood episode between the tianeptine and placebo groups. We also assessed overall functioning, biological rhythms, quality of life, rates of manic switch and serum brain-derived neurotrophic factor levels. Results: There were no differences between adjunctive tianeptine or placebo regarding time to intervention or depression scores in the 24-week double-blind controlled phase. Patients in the tianeptine group showed better performance in the letter-number sequencing subtest from the Wechsler Adult Intelligence Scale at the endpoint ( p =0.014). Tianeptine was well tolerated and not associated with higher risk for manic switch compared to placebo. Conclusion: Tianeptine was not more effective than placebo in the maintenance treatment of bipolar depression. There is preliminary evidence suggesting a pro-cognitive effect of tianeptine in working memory compared to placebo.